Kinetika Reaksi Proses Pirolisis Pada Sekam Padi: Casnan, Erliza Noor, Hartrisari Hardjomidjojo, Irzaman, dan Eti Rohaeti - Casnan Casnan; Erliza Noor Erliza Noor; Hartrisari Hardjomidjojo Hartrisari Hardjomidjojo; Irzaman Irzaman; Eti Rohaeti Eti Rohaeti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
This study aims to determine the reaction kinetics of the rice husk pyrolysis process by analyzing the characteristics of the Thermogravimetry Analysis (TGA) curve. Characteristics of the TGA Curve describes the process of losing mass to the temperature in the pyrolysis process with various stages of material phase changes due to the heating process. The pyrolysis process is influenced by temperature, time, and heating rate, so by analyzing the temperature, time and heating rates, the reaction kinetics will be obtained. The kinetic reaction of the pyrolysis process based on the Arrhenius equation, the speed of the decomposition reaction is influenced by changes in mass or mass fraction per unit time. Exponential factor value (A) will affect the speed of reaction of the pyrolysis process, the greater the value of A, the greater the reaction speed and vice versa. Value (A) in the pyrolysis process of HCl washed and heated rice husk, the value is smaller when compared with the value of A process of rice husk pyrolysis without washing and heating.